Pengaruh Faktor Keluarga dan Teman Sebaya terhadap Minat Mahasiswa Memilih Program Studi Manajemen Pendidikan Islam di STIT Palapa Nusantara Lombok - NTB - Muhamad Zaril Gapari (Manajemen Pendidikan Islam STIT Palapa Nusantara, 2022)
Interest is a tendency to give encouragement in paying attention to something that has an influence on experience or a tendency that makes the subject feel interested in something. Interest which is accompanied by a sense of pleasure in education and the work that is aspired to be one of the factors that encourage individuals to decide to choose a study program. So if the individual chooses a study program according to their interests, it can bring better results in their career or future because with the interest to continue their higher education , it is hoped that later they can be a stepping stone to get a better future than before. This phenomenon is the determining process in choosing a study program. This study aims to determine the influence of family factors on student interest in choosing Islamic Education Management study program and to determine the influence of peer factors on student interest in choosing Islamic Education Management study program. This type of research is quantitative research with a causal associative approach. The research population was all students of the Islamic Education Management study program. Sampling using proportional random sampling technique. This research instrument used is a questionnaire (questionnaire). This research uses multiple linear regression data analysis technique using the SPSS for windows version 18 calculation tool. The results showed that the family factor (X1) did not have a significant effect on the students' interest in choosing the Islamic Education Management study program and the peer factor (X2) had a significant positive influence on the students' interest in choosing the Islamic Education Management study program at STIT Palapa Nusantara Lombok – NTB. Based on the results of the study, it can be concluded that the family factor variable is not able to explain well the high and low interest of students choosing the Islamic Education Management study program and the peer factor variable is able to explain well the high and low interest of students choosing the Islamic Education Management study program at STIT Palapa Nusantara Lombok - NTB . This study provides information that family factors have no significant effect on students' interest in choosing an economic education study program.